PERTUMBUHAN EKONOMI DITINJAU DARI PENGGUNAAN INVESTASI, TENAGA KERJA DAN BELANJA PEMERINTAH - Isnowati, Sri; Masdjojo, Gregorius N; Fauzan, Mohammad (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This research aims to examine the influence of investment, labor and government spending on economic growth in Central Java Province. The data used in this research is secondary data published by the Central Statistics Agency (BPS) and Bank Indonesia. The data used in this research is pooled data from 35 districts/cities in Central Java Province from 2017 to 2021. The analytical tool used is multiple regression analysis with panel data. The results of data analysis show that investment, labor and government spending have a positive influence on economic growth in Central Java both individually and together.